A semiotic approach to the study of emojis - Vela Delfa, Cristina (Círculo de Lingüística Aplicada a la Comunicación, 2020)
Emojis are graphic signs that are frequently used in written digital interactions. Although they have become increasingly popular since they were incorporated into the Apple keyboard in 2011 and instant messaging applications such as WhatsApp, their origin can be traced back to the 1990’s. In recent years, emojis have emerged as one of the central topics in digital communication studies and have been approached from different fields and theories. In this work, we present a semiotic characterization of emojis. We ask ourselves about the place that these elements occupy in the classification of signs (index, icon, symbol), how their interpretation is constructed and what relationships these communicative units establish between each other.